Origin of nitrogen on Mars: First in situ N isotope analyses of martian meteorites. (1st March 2023) - Deligny, C.; Füri, E.; Deloule, E.; Peslier, A.H.; Faure, F.; Marrocchi, Y.
Abstract: Martian meteorites are key for assessing the isotopic characteristics of nitrogen in different martian reservoirs (i.e., mantle, crust, and atmosphere), and, ultimately, for constraining the source(s) of nitrogen trapped during the earliest stages of planetary accretion in the terrestrial planet-forming region. In this study, we analysed, for the first time, the nitrogen content and isotopic composition of glassy melt inclusions of Chassigny and of the mesostasis of five nakhlites (MIL 03346, Nakhla, NWA 6148, NWA 998, and Y 000593) by in situ secondary ion mass spectrometry. The nitrogen content of Chassigny melt inclusions, corrected for olivine overgrowth on the inclusion walls, varies from 4 ± 1 to 860 ± 45 ppm N, and the majority of δ 15 N values range from –35 ± 41 to +73 ± 36‰. The estimated nitrogen isotopic signature of the primitive melt, prior to degassing of N2 or NH3, is 0 ± 32‰. The mesostasis of nakhlites contains 2.7 ± 0.2 to 943 ± 156 ppm N, with δ 15 N values from –30 ± 37 to +348 ± 43‰. Whereas degassing of N2 or NH3 can explain the lowest nitrogen isotopic ratios measured in the nakhlite mesostasis, the 15 N-enriched isotopic composition (δ 15 N > 150‰) of four nakhlites (MIL 03346, Nakhla, NWA 6148, and Y 000593) likely results from interaction of the mesostasis melt with the martian atmosphere during ejection. The δ 15 N values (+25 ± 42 and +77 ± 19‰) of two melt inclusions in Y 000593 are comparable to those of Chassigny, further confirming that these meteorites likely sample a common volatile reservoir in the martian interior. Overall, the new results indicate that the chassignite-nakhlite reservoir did not inherit nitrogen from the solar nebula but, instead, from chondritic-like materials. These findings further confirm that planetary bodies in the inner solar system accreted (isotopically) chondritic nitrogen during the first few million years of solar system history.